2008
DOI: 10.1164/rccm.200801-086oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 and Th17 Cells Enhance Th2-Cell–mediated Eosinophilic Airway Inflammation in Mice

Abstract: IL-23 and Th17 cells not only induce Th17-cell-mediated neutrophilic airway inflammation but also up-regulate Th2-cell-mediated eosinophilic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
315
4
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(352 citation statements)
references
References 42 publications
28
315
4
5
Order By: Relevance
“…Blocking of IL-23 during the coculture of Per a 10 stimulated BMDCs and naive T cells reduced the secretion of Th2 type cytokines, implicating its role in protease induced Th2 responses. Our results are in accordance with a previous study where neutralization of IL-23 has led to reduction in Th2 cytokine production [32].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Blocking of IL-23 during the coculture of Per a 10 stimulated BMDCs and naive T cells reduced the secretion of Th2 type cytokines, implicating its role in protease induced Th2 responses. Our results are in accordance with a previous study where neutralization of IL-23 has led to reduction in Th2 cytokine production [32].…”
Section: Discussionsupporting
confidence: 94%
“…Blocking of IL-23 during the coculture of Per a 10 stimulated BMDCs and naive T cells reduced the secretion of Th2 type cytokines, implicating its role in protease induced Th2 responses. Our results are in accordance with a previous study where neutralization of IL-23 has led to reduction in Th2 cytokine production [32].Though immunotherapy with inactive Per a 10 was more effective than that of active Per a 10 in both cockroach extract sensitized [17] and Per a 10 sensitized mice the underlying mechanism remained to be elusive. Higher levels of IL-12p70 in the BALF of inactive Per a 10 immunized mice along with its higher secretion by inactive Per a 10 stimulated BMDCs might be a reason for the efficacy of inactive Per a 10 in immunotherapy.…”
supporting
confidence: 92%
“…Hence passive transfer of CD47 high but not CD47 low polyclonal CD4 T cells induced eosinophilia and lung inflammation after 4 wk in nonlymphopenic mice. In support of our observations, adoptive transfer of in vitrogenerated Ag-specific Th17 cells initiates neutrophil recruitment in the airways with no inflammation, whereas cotransfer of Th17 and Th2 cell lines is required to promote a mixed neutrophilic and eosinophilic infiltration and airway hyperreactivity (AHR) (34). Collectively, our data favor the concept that Th17/Th2 doubleproducing cells, which are found in increased proportion in the circulation of patients with severe asthma (35) and identified as CD47 high in this study, are pathogenic and drive airway disease.…”
Section: Discussionsupporting
confidence: 72%
“…8). Furthermore, Wakashin et al (57) have reported that IL-23-mediated enhancement of Ag-induced neutrophil recruitment in the airway was reduced by the absence of IL-17, suggesting that IL-23 also contributes to neutrophilic airway inflammation through IL-17 production in this model.…”
Section: Discussionmentioning
confidence: 80%